Functional Analysis of the Sex Related Gene dmrt1 in Xenopus - Kukoly, Lindsey (My University, 2023)
Sex determination is a key developmental process in several species regulated by sexrelated transcription factors. In many species a gene called doublesex and mab-3 related transcription factor 1 (dmrt1), plays an important role in sexual differentiation. I used African clawed frogs (Xenopus) to examine function of dmrt1 in two species: a diploid species, X. tropicalis, and an allotetraploid species, X. laevis. In both species, dmrt1 is an autosomal gene; Xenopus tropicalis has one copy of dmrt1 and X. laevis has two homeologous copies that by definition are derived from whole genome duplication: dmrt1.L and dmrt1.S in X. laevis. We generated knockouts of each of these genes to further examine their function in sexual differentiation. Histological examination showed testicular dysgenesis in X. tropicalis dmrt1 and X. laevis dmrt1.L null males whereas dmrt1.S null males presented no obvious difference in sperm density compared to wildtype males. X. tropicalis dmrt1 and X. laevis dmrt1.L null females were found to completely lack reproductive organs and are infertile whereas dmrt1.S null females appeared unaffected. The contrasting results between dmrt1.L and dmrt1.S in X. laevis provides evidence of both neofunctionalization and subfunctionalization following gene duplication and suggest that gene duplication is a major contributor to evolutionary change. Additional investigation of the transcriptome of these frogs and the role of dmrt1 in the secondary sex characteristic vocalization provides further evidence of the role of dmrt1 in development. Comprehensively, this investigation provides further knowledge of the role of dmrt1 and homeologs of this gene in sexual differentiation and introduces a novel aspect of this gene in female development. Future efforts are focused on generating double knockouts for dmrt1.L and dmrt1.S, further examining the role of dmrt1.S in somatic cell function and developing additional mutant lines in other Xenopus for comparative analysis.
Mechanistic investigation of the sex related gene dmrt1 in African clawed frogs (Xenopus) evidences both neofunctionalization and subfunctionalization
Keywords: Xenopus laevis; Xenopus tropicalis; Sex determination; Evolutionary genetics; doublesex and mab-3 related transcription factor 1 (dmrt1)